A novel complex of membrane proteins required for formation of a spherical nucleus - Siniossoglou, Symeon; Santos-Rosa, Helena; Rappsilber, Juri; Mann, Mathias; Hurt, Ed (The EMBO journal, 1998)
Two membrane proteins were identified through their genetic interaction with the nucleoporin Nup84p and shown to participate in nuclear envelope morphogenesis in yeast. One component is a known sporulation factor Spo7p, and the other, Nem1p, a novel protein whose C‐terminal domain is conserved during eukaryotic evolution. Spo7p and Nem1p localize to the nuclear/ER membrane and behave biochemically as integral membrane proteins. Nem1p binds to Spo7p via its conserved C‐terminal domain. Although cells without Spo7p or Nem1p are viable, they exhibit a drastically altered nuclear morphology with long, pore‐containing double nuclear membrane extensions. These protrusions emanate from a core nucleus which contains the DNA, and penetrate deeply into the cytoplasm. Interestingly, not only Spo7− and Nem1−, but also several nucleoporin mutants are defective in sporulation. Thus, Spo7p and Nem1p, which exhibit a strong genetic link to nucleoporins of the Nup84p complex, fulfil an essential role in formation of a spherical nucleus and meiotic division.
Gesehen am 01.12.2025